Satisfaction with paper-based dental records and perception of electronic dental records among dental professionals in Myanmar - Thu, S; Kijsanayotin, B; Kaewkungwal, J; Soonthornworasiri, N; Pan-Ngum, W (Korean Society of Medical Informatics, 2017)
Objectives To overcome challenges in the implementation of electronic dental record systems in a low-resource setting, it is crucial to know the level of users’ satisfaction with the existing system of paper-based dental records and their perceptions of electronic dental records. Methods A cross-sectional paper-based questionnaire survey was conducted among Myanmar dental professionals who worked in one of two teaching hospitals or in private dental clinics. Descriptive data were analyzed and regression analysis was carried out to identify factors influencing perceptions of electronic dental records. Results Most dental professionals (>60%) were satisfied with just three out of six aspects of paper-based dental records (familiarity, flexibility, and portability). In addition, generalized positive perceptions were found among decision makers towards electronic dental records, and 86% of dentists indicated that they were willing to use them. Financial concerns were identified as the most important barrier to the implementation of electronic dental records among dentists who were not willing to use the proposed system. Conclusions The first step towards implementing electronic dental records in Myanmar should be improvement of the content and structure of paper-based dental records, especially in private dental clinics. Utilization of appropriate open-source electronic dental record software in private dental clinics is recommended to address perceived issues around financial barriers. For the long term, we recommend providing further education and training in health informatics to healthcare professionals to facilitate the efficient use of electronic dental record software in Myanmar in the future.